Baldwin777
2x^2+4x=16
x=?
Delete
Share
This Question is Closed
pottersheep
Best Response
You've already chosen the best response.
2
Rearrange it to become
2x^2+4x - 16 = 0
Then plug it into the formula or factor it
pottersheep
Best Response
You've already chosen the best response.
2
You can factor out a 2, see where that gets you..
pottersheep
Best Response
You've already chosen the best response.
2
Do you get it?
Baldwin777
Best Response
You've already chosen the best response.
1
no,I don't
pottersheep
Best Response
You've already chosen the best response.
2
it becomes
2(x^2 + 2x - 8) = 0
when you factor it
pottersheep
Best Response
You've already chosen the best response.
2
Can you factor x^2 + 2x - 8 ?
Baldwin777
Best Response
You've already chosen the best response.
1
okay let me try this
Baldwin777
Best Response
You've already chosen the best response.
1
it would be (x+4)(x-2) right?
pottersheep
Best Response
You've already chosen the best response.
2
Do you know the formula? The quadratic formula?
Baldwin777
Best Response
You've already chosen the best response.
1
Yes and no, I forgot the steps
pottersheep
Best Response
You've already chosen the best response.
2
Nice you factored it right
Baldwin777
Best Response
You've already chosen the best response.
1
So then I would plug the x+4 and x-2 into the equation right,? it would be 2(4)^2+4(-2)=16??
pottersheep
Best Response
You've already chosen the best response.
2
So
2(x^2 + 2x - 8) = 0
2 (x - 2 ) ( x + 4 ) = 0
NOW, you know how anything times zero = 0?
You have to make at least one of the brackets = 0 to get zero as an overall answer. So what can we put as x to make the brackets zero? There is x in two places so there are 2 answers
pottersheep
Best Response
You've already chosen the best response.
2
To find the answers, factoring is one way. The formula is another. Yo chose to factor so you dont need to use the formula anymore
Baldwin777
Best Response
You've already chosen the best response.
1
2x-2=0 and 2x+4=0
pottersheep
Best Response
You've already chosen the best response.
2
You just have to make the brackets = 0, don't put in the two!
See we got
2 (x - 2 ) ( x + 4 ) = 0
So, one bracket is
(x-2) . We want to make this = 0
x-2 = 0
x = 2 !!! One of the answers..
Next bracket
(x+4)
Make it equal to zero.
x+4 = 0
x= -4
So the answer is x = -4 or x = 2
Baldwin777
Best Response
You've already chosen the best response.
1
oh wow, that was really simple, Now I under stand
pottersheep
Best Response
You've already chosen the best response.
2
Yay!! :)
Baldwin777
Best Response
You've already chosen the best response.
1
Thank u
pottersheep
Best Response
You've already chosen the best response.
2
you're welcome